COSTS FOR THE SURGICAL TREATMENT OF OBESITY THROUGH LAPAROSCOPY IN A FEDERAL TERTIARY HOSPITAL BY THE BRAZILIAN UNIFIED HEALTH SYSTEM - Álvaro Antonio Bandeira FERRAZ; Hiago Dantas MEDEIROS; Fernando SANTA-CRUZ; Flávio KREIMER (ABCD: Arquivos Brasileiros de Cirurgia Digestiva, 2024)
ABSTRACT BACKGROUND: Obesity is a multifactorial disease affecting a significant portion of the population. Bariatric surgery emerges as a prominent approach in this context, representing an effective treatment both in the short and long term. The costs associated with bariatric surgery vary depending on the characteristics of the patients, current hospital practices, and available funding sources. AIMS: To analyze the costs of minimally invasive bariatric surgery for the treatment of obesity in a tertiary federal public hospital. METHODS: An observational and descriptive study aimed at assessing the costs associated with laparoscopic vertical gastrectomy (GV) and Roux-en-Y gastric bypass (RYGB) in a federal public tertiary service from 2018 to 2021. Data were obtained through the management of medical-hospital expenses related to surgical and anesthetic supplies, as well as the amount reimbursed by the funding source to the hospital. RESULTS: Over the analyzed period, a total of 177 minimally invasive bariatric surgeries were performed. In terms of the charges, since 2018, the hospital has been receiving an amount of R$ 6,145.00 for the “bariatric surgery by videolaparoscopy” procedure, which includes RYGB, and R$ 4,095.00 for “vertical gastrectomy.” Regarding the average hospital cost of surgical supplies, RYGB incurred a total of R$ 9,907.54, while GV incurred a total of R$ 9,315.84. The average total cost of RYGB was R$ 10,799.23, and, for GV, it was R$ 10,207.53. These figures indicate that the hospital incurred a loss of approximately R$ 4,654.23 for performing RYGB and R$ 6,112.53 for GV. CONCLUSION: Despite the increasing number of eligible patients for surgical treatment of obesity and the consequent quantitative growth of these procedures funded by the Brazilian Unified Health System (SUS), the costs exceed the reimbursement from the funding source in federal public hospitals. There is a need for a precise assessment of financing in the fight against obesity.